A TEM study of Ni interfaces formed during activation of SOFC anodes in H2: Influence of grain boundary symmetry and segregation of impurities. (15th January 2016) - Jeangros, Q.; Aebersold, A.B.; Hébert, C.; Van Herle, J.; Hessler-Wyser, A.
Abstract: The electrochemical properties of a solid oxide fuel cell depend on many parameters, including – on the anode side – the connectivity of the Ni network and the segregation of impurities at active points. In this work, advanced scanning transmission electron microscopy techniques are employed to assess 1) the influence of the symmetry of NiO/NiO grain boundaries on the percolation of the Ni phase after activation and 2) the segregation of impurities at these new Ni interfaces that form during NiO reduction. Automated crystal orientation mapping in the transmission electron microscope reveals that coherent NiO twin boundaries remain intact during reduction, while NiO grains separated by an incoherent boundary detach from each other when reducing to Ni. Small Ni domains twinned with respect to the larger Ni grains are also observed to form during reduction of the NiO phase. Energy-dispersive X-ray spectroscopy reveals that Al and Si impurities, which are present in the raw materials, may block electrochemically active points of the anode by segregating in the form of a glassy film at the interfaces/surfaces that appeared during activation. This oxidised film supports Ni nanoparticles that precipitated from volatile Ni hydroxide. Graphical abstract: